Improving Students' Science Literacy Skills through Treasure Hunting Games with Problem Based Learning Model - Farah Albi Febianti; Wati Sukmawati (Jurnal Penelitian Pendidikan IPA, 2024)
This study aims to evaluate the impact of the Problem Based Learning (PBL) model with a treasure hunt game strategy on improving students' scientific literacy skills. The research method employed a quasi-experimental approach with a pretest-posttest control group design. The subjects consisted of two classes: an experimental class implementing the PBL model with the treasure hunt game strategy and a control class using conventional teaching methods. Data were collected through scientific literacy tests administered before and after the intervention and analyzed using stacking and racking analysis based on the Rasch Model. The results indicated that both classes experienced an increase in scientific literacy skills, with the experimental class showing a higher average increase of 1.99 compared to the control class's 1.80. Although the percentage difference in improvement was only about 11.24%, this suggests that the PBL method with the game strategy can provide additional positive contributions to science learning. The discussion highlights the importance of proper method implementation, teacher-student interaction, and learning environment conditions in influencing learning outcomes. In conclusion, while the PBL method with the game strategy is effective in enhancing scientific literacy, a holistic approach is still needed for optimal development of students' abilities.